The Extract of Ziziphus jujuba Fruit (Jujube) Induces Expression of Erythropoietin Via Hypoxia-Inducible Factor-1α in Cultured Hep3B Cells - Chen, Jianping; Lam, Candy T. W.; Kong, Ava Y. Y.; Zhang, Wendy L.; Zhan, Janis Y. X.; Bi, Cathy W. C.; Chan, Gallant K. L.; Lam, Kelly Y. C.; Yao, Ping; Dong, Tina T. X.; Tsim, Karl W. K. (Planta Medica, 2014)
The fruit of Ziziphus jujuba Mill., known as jujube or Chinese date, is commonly consumed as health supplement or herbal medicine worldwide. To study the beneficial role of jujube in enhancing hematopoietic function, we investigated its roles on the expression of erythropoietin in cultured Hep3B human hepatocellular carcinoma cells. Application of chemically standardized jujube water extract stimulated erythropoietin expression in a dose-dependent manner, with the highest response by ~ 100 % of increase. A plasmid containing hypoxia response element, a critical regulator for erythropoietin transcription, was transfected into Hep3B cells. Application of jujube water extract onto the transfected cells induced the transcriptional activity of the hypoxia response element. To account for its transcriptional activation, the expression of hypoxia-inducible factor-1α was increased after treatment with jujube water extract: the increase was in both mRNA and protein levels. These results confirmed the hematopoietic function of jujube in the regulation of erythropoietin expression in liver cells.
Keywords: Ziziphus jujuba; Rhamnaceae; erythropoietin; hypoxia response element; hypoxia-inducible factor